La danza en el desarrollo psicosocial, de los niños de 4 a 5 años del centro de educación inicial “Casa de la Cultura, ciudad de Puyo”, cantón y provincia de Pastaza, durante el año lectivo 2.010 – 2.011 - Guamán Segovia, Luz Aurora (2016)
Psychosocial development is based on a number of factors involving both people and the environment that surrounds them. Therefore, development in children is a project that needs to be fulfilled certain conditions and care, and that is affected when their needs are not covered and adequately addressed. Thus, we find children who have suffered and / or suffer deficiencies and risks that threaten their development, affecting their mental health in various areas underlying personality. This problem was evident in this investigation as to raise the issue of whether dance influences psychosocial development was established that children Center beneficiary of this study Early Childhood Education, do not enjoy the process of comprehensive psychosocial development enough to educate through dance, you need both theoretical knowledge and practical, between the two must be a proper balance in the system of artistic influences. The first helps the individual to analyze what really have artistic value; enables skills to discover imperceptible details for the individual not educated artistically; raises the personal aesthetic taste, and provides the knowledge of the historical development of the demonstration. Dance in the psychosocial development is an activity of fundamental importance within the creative learning; encourages the development at the physical level: as it helps in blood circulation, develops motor coordination body, increases flexibility, among other benefits, emotional and mental level builds confidence, unlock tension and emotions of stress, helps discover their own essence. As described above is not met fully in this Educational Center, reason why after establishing the real problems could make a proposal that meets and contributes to solve the problem encountered, which will serve for immediate application in the mentioned Center, as well as reference material for those who wish to do so. As considers this priority investigation as concerns the psychosocial development of children and child.